Cardiovascular dysfunction in infants with neonatal encephalopathy. Issue 4 (27th July 2011) - Armstrong, Katey; Franklin, Orla; Sweetman, Deirdre; Molloy, Eleanor J
Abstract : Severe perinatal asphyxia with hypoxic ischaemic encephalopathy occurs in approximately 1–2/1000 live births and is an important cause of cerebral palsy and associated neurological disabilities in children. Multiorgan dysfunction commonly occurs as part of the asphyxial episode, with cardiovascular dysfunction occurring in up to a third of infants. This narrative paper attempts to review the literature on the importance of early recognition of cardiac dysfunction using echocardiography and biomarkers such as troponin and brain type natriuretic peptide. These tools may allow accurate assessment of cardiac dysfunction and guide therapy to improve outcome.